REPRESENTASI ‘KEKERASAN SIMBOLIK’ DALAM FOTO IKLAN: STUDI KASUS FOTO IKLAN CETAK PRODUK KECANTIKAN PEREMPUAN DALAM MAJALAH FEMINA TAHUN 2000 - Fitriana Fitriana; Soeprapto Soedjono; Kusrini Kusrini (Specta: Journal of Photography, Arts, and Media, 2021)
Representation of ‘Symbolic Violence’ in Printed Advertisement Photo of Beauty Product in Femina Magazine Issue 2000. This study examines the representation of ‘symbolic violence’ in several advertisement photos in Femina magazine in 2000. The research used qualitative methods that focus on the discourse and value of advertised beauty products. Purposive sampling technique was used to choose the samples of the study. There are three advertisement photos that were re- viewed. The theories used in this study such as ‘symbolic violence’, representation, advertisement photography, and gender ideology were used in this study. Meanwhile, overall, the perspective of the research applied the gender approach. This is about the limitation of the research object that used female photo subjects associated with ‘symbolic violence’ represented in the verbal aspects such as headline, body copy, slogan, etc.. The results of the study were the discovery of forms of ‘symbolic violence’ in advertisement photo samples, such as the ideal construction of beauty, the culture of consumerism, the imposition of product information on consumers, and the domestication of women. ABSTRAKPenelitian ini membahas representasi ‘kekerasan simbolik’ dalam beberapa foto iklan di majalah Femina tahun 2000. Penelitian menggunakan metode kualitatif yang berfokus pada wacana maupun nilai dari produk kecantikan yang diiklankan. Pengambilan sampel menggunakan teknik purposive sampling. Terdapat tiga buah foto iklan yang dikaji. Teori yang digunakan adalah teori ‘kekerasan simbolik’, representasi, fotografi periklanan, dan ideologi gender.Secara keseluruhan, perspektif penelitian lebih berorientasi pada pendekatan gender. Hal ini tidak lepas dari pembatasan objek penelitian terkait ‘kekerasan simbolik’ yang terepresentasi pada subjek foto perempuan, termasuk aspek verbal seperti  head line, body copy, dan slogan. Hasil penelitian berupa ditemukannya bentuk-bentuk ‘kekerasan simbolik’ dalam sampel foto, seperti konstruksi ideal kecantikan, budaya konsumerisme, ‘pemaksaan’ informasi produk kepada konsumen, hingga domestikasi perempuan.